Validation of the Model of End-Stage Liver Disease for Liver Transplant Allocation in Alberta: Implications for Future Directions in Canada - Kelly W. Burak; Glenda A. Meeberg; Robert P. Myers; Gordon H. Fick; Mark G. Swain; Vincent G. Bain; Norman M. Kneteman; Robert J. Hilsden (Canadian Journal of Gastroenterology and Hepatology)
Background. Since 2002, the Model of End-Stage Liver Disease (MELD) has been used for allocation of liver transplants (LT) in the USA. In Canada, livers were allocated by the CanWAIT algorithm. The aim of this study was to compare the abilities of MELD, Child-Pugh (CP), and CanWAIT status to predict 3-month and 1-year mortality before LT in Canadian patients and to describe the use of MELD in Canada. Methods. Validation of MELD was performed in 320 patients listed for LT in Alberta (1998–2002). In October 2014, a survey of MELD use by Canadian LT centers was conducted. Results. Within 1 year of listing, 47 patients were removed from the waiting list (29 deaths, 18 too ill for LT). Using logistic regression, the MELD and CP were better than the CanWAIT at predicting 3-month (AUROC: 0.79, 0.78, and 0.59; p=0.0002) and 1-year waitlist mortality (AUROC: 0.70, 0.70, and 0.55; p=0.0023). Beginning in 2004, MELD began to be adopted by Canadian LT programs but its use was not standardized. Conclusions. Compared with the CanWAIT system, the MELD score was significantly better at predicting LT waitlist mortality. MELD-sodium (MELD-Na) has now been adopted for LT allocation in Canada.